Pengaruh Budaya Organisasi, Reward dan Punishment Terhadap Kinerja Pegawai dengan Motivasi Kerja Sebagai Variabel Intervening pada ASN di Lingkup Sekretariat Daerah Kabupaten Kerinci (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the influence of organisational culture, rewards, and punishments on employee performance with work motivation as an intervening variable among civil servants (ASN) in the Kerinci Regency Regional Secretariat. The study uses a quantitative approach with a survey method. Data were collected through the distribution of structured questionnaires to all 85 ASN using a saturated sampling technique. The research instrument was developed using a Likert scale to measure respondents' perceptions of organisational culture, rewards, punishments, work motivation, and employee performance. Data analysis was performed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) using the SmartPLS application to test the direct and indirect effects between variables. The results showed that organisational culture and rewards had a positive and significant effect on work motivation and employee performance. Conversely, punishment did not have a significant effect on work motivation or employee performance. Work motivation was found to have a positive and significant effect on performance and was able to mediate the relationship between organisational culture and employee performance, but it did not mediate the relationship between rewards and punishment and performance.